Задание № 1
![x^{3}+x^{2}+x+1=(x^{3}+x^{2})+(x+1)=x^{2}(x+1)+(x+1)=x^{2}(x+1)+1(x+1)=(x+1)(x^{2}+1) x^{3}+x^{2}+x+1=(x^{3}+x^{2})+(x+1)=x^{2}(x+1)+(x+1)=x^{2}(x+1)+1(x+1)=(x+1)(x^{2}+1)](https://tex.z-dn.net/?f=x%5E%7B3%7D%2Bx%5E%7B2%7D%2Bx%2B1%3D%28x%5E%7B3%7D%2Bx%5E%7B2%7D%29%2B%28x%2B1%29%3Dx%5E%7B2%7D%28x%2B1%29%2B%28x%2B1%29%3Dx%5E%7B2%7D%28x%2B1%29%2B1%28x%2B1%29%3D%28x%2B1%29%28x%5E%7B2%7D%2B1%29)
======================================================================
![y^{5}-y^{3}-y^{2}+1=(y^{5}-y^{3})+(-y^{2}+1)=(y^{5}-y^{3})-(y^{2}-1)=y^{3}(y^{2}-1)-(y^{2}-1)=y^{3}(y^{2}-1)-1(y^{2}-1)=(y^{2}-1)(y^{3}-1) y^{5}-y^{3}-y^{2}+1=(y^{5}-y^{3})+(-y^{2}+1)=(y^{5}-y^{3})-(y^{2}-1)=y^{3}(y^{2}-1)-(y^{2}-1)=y^{3}(y^{2}-1)-1(y^{2}-1)=(y^{2}-1)(y^{3}-1)](https://tex.z-dn.net/?f=y%5E%7B5%7D-y%5E%7B3%7D-y%5E%7B2%7D%2B1%3D%28y%5E%7B5%7D-y%5E%7B3%7D%29%2B%28-y%5E%7B2%7D%2B1%29%3D%28y%5E%7B5%7D-y%5E%7B3%7D%29-%28y%5E%7B2%7D-1%29%3Dy%5E%7B3%7D%28y%5E%7B2%7D-1%29-%28y%5E%7B2%7D-1%29%3Dy%5E%7B3%7D%28y%5E%7B2%7D-1%29-1%28y%5E%7B2%7D-1%29%3D%28y%5E%7B2%7D-1%29%28y%5E%7B3%7D-1%29%C2%A0)
======================================================================
![a^{4}+2a^{3}-a-2=(a^{4}-a)+(2a^{3}-2)=a(a^{3}-1)+2(a^{3}-1)=(a^{3}-1)(a+2) a^{4}+2a^{3}-a-2=(a^{4}-a)+(2a^{3}-2)=a(a^{3}-1)+2(a^{3}-1)=(a^{3}-1)(a+2)](https://tex.z-dn.net/?f=a%5E%7B4%7D%2B2a%5E%7B3%7D-a-2%3D%28a%5E%7B4%7D-a%29%2B%282a%5E%7B3%7D-2%29%3Da%28a%5E%7B3%7D-1%29%2B2%28a%5E%7B3%7D-1%29%3D%28a%5E%7B3%7D-1%29%28a%2B2%29)
======================================================================
![b^{6}-3b^{4}-2b^{2}+6=(b^{6}-2b^{2})+(-3b^{4}+6)=(b^{6}-2b^{2})-(3b^{4}-6)=b^{2}(b^{4}-2)-3(b^{4}-2)=(b^{4}-2)(b^{2}-3) b^{6}-3b^{4}-2b^{2}+6=(b^{6}-2b^{2})+(-3b^{4}+6)=(b^{6}-2b^{2})-(3b^{4}-6)=b^{2}(b^{4}-2)-3(b^{4}-2)=(b^{4}-2)(b^{2}-3)](https://tex.z-dn.net/?f=b%5E%7B6%7D-3b%5E%7B4%7D-2b%5E%7B2%7D%2B6%3D%28b%5E%7B6%7D-2b%5E%7B2%7D%29%2B%28-3b%5E%7B4%7D%2B6%29%3D%28b%5E%7B6%7D-2b%5E%7B2%7D%29-%283b%5E%7B4%7D-6%29%3Db%5E%7B2%7D%28b%5E%7B4%7D-2%29-3%28b%5E%7B4%7D-2%29%3D%28b%5E%7B4%7D-2%29%28b%5E%7B2%7D-3%29)
======================================================================
![a^{2}-ab-8a+8b=(a^{2}-ab)+(-8a+8b)=(a^{2}-ab)-(8a-8b)=a(a-b)-8(a-b)=(a-b)(a-8) a^{2}-ab-8a+8b=(a^{2}-ab)+(-8a+8b)=(a^{2}-ab)-(8a-8b)=a(a-b)-8(a-b)=(a-b)(a-8)](https://tex.z-dn.net/?f=a%5E%7B2%7D-ab-8a%2B8b%3D%28a%5E%7B2%7D-ab%29%2B%28-8a%2B8b%29%3D%28a%5E%7B2%7D-ab%29-%288a-8b%29%3Da%28a-b%29-8%28a-b%29%3D%28a-b%29%28a-8%29%C2%A0)
======================================================================
![ab-3b+b^{2}-3a=(ab+b^{2})+(-3b-3a)=(ab+b^{2})-(3b+3a)=(ab+b^{2})-(3a+3b)= b(a+b)-3(a+b)=(a+b)(b-3) ab-3b+b^{2}-3a=(ab+b^{2})+(-3b-3a)=(ab+b^{2})-(3b+3a)=(ab+b^{2})-(3a+3b)= b(a+b)-3(a+b)=(a+b)(b-3)](https://tex.z-dn.net/?f=ab-3b%2Bb%5E%7B2%7D-3a%3D%28ab%2Bb%5E%7B2%7D%29%2B%28-3b-3a%29%3D%28ab%2Bb%5E%7B2%7D%29-%283b%2B3a%29%3D%28ab%2Bb%5E%7B2%7D%29-%283a%2B3b%29%3D+b%28a%2Bb%29-3%28a%2Bb%29%3D%28a%2Bb%29%28b-3%29)
======================================================================
![11x-xy+11y-x^{2}=(11x+11y)+(-xy-x^{2})=(11x+11y)-(xy+x^{2})=11(x+y)-x(y+x)=(x+y)(11-x) 11x-xy+11y-x^{2}=(11x+11y)+(-xy-x^{2})=(11x+11y)-(xy+x^{2})=11(x+y)-x(y+x)=(x+y)(11-x)](https://tex.z-dn.net/?f=11x-xy%2B11y-x%5E%7B2%7D%3D%2811x%2B11y%29%2B%28-xy-x%5E%7B2%7D%29%3D%2811x%2B11y%29-%28xy%2Bx%5E%7B2%7D%29%3D11%28x%2By%29-x%28y%2Bx%29%3D%28x%2By%29%2811-x%29)
======================================================================
![kn-mn-n^{2}+mk=(kn-n^{2})+(mk-mn)=n(k-n)+m(k-n)=(k-n)(n+m) kn-mn-n^{2}+mk=(kn-n^{2})+(mk-mn)=n(k-n)+m(k-n)=(k-n)(n+m)](https://tex.z-dn.net/?f=kn-mn-n%5E%7B2%7D%2Bmk%3D%28kn-n%5E%7B2%7D%29%2B%28mk-mn%29%3Dn%28k-n%29%2Bm%28k-n%29%3D%28k-n%29%28n%2Bm%29)
======================================================================
Задание № 2
![ab-8a-bx+8x=(ab-bx)+(-8a+8x)=(ab-bx)-(8a-8x)=b(a-x)-8(a-x)=(a-x)(b-8) ab-8a-bx+8x=(ab-bx)+(-8a+8x)=(ab-bx)-(8a-8x)=b(a-x)-8(a-x)=(a-x)(b-8)](https://tex.z-dn.net/?f=ab-8a-bx%2B8x%3D%28ab-bx%29%2B%28-8a%2B8x%29%3D%28ab-bx%29-%288a-8x%29%3Db%28a-x%29-8%28a-x%29%3D%28a-x%29%28b-8%29)
======================================================================
![ax-b+bx-a=(ax+bx)+(-b-a)=(ax+bx)-(b+a)=(ax+bx)-(a+b)=x(a+b)-(a+b)=x(a+b)-1(a+b)=(a+b)(x-1) ax-b+bx-a=(ax+bx)+(-b-a)=(ax+bx)-(b+a)=(ax+bx)-(a+b)=x(a+b)-(a+b)=x(a+b)-1(a+b)=(a+b)(x-1)](https://tex.z-dn.net/?f=ax-b%2Bbx-a%3D%28ax%2Bbx%29%2B%28-b-a%29%3D%28ax%2Bbx%29-%28b%2Ba%29%3D%28ax%2Bbx%29-%28a%2Bb%29%3Dx%28a%2Bb%29-%28a%2Bb%29%3Dx%28a%2Bb%29-1%28a%2Bb%29%3D%28a%2Bb%29%28x-1%29)
======================================================================
![ax-y+x-ay=(ax-ay)+(-y+x)=(ax-ay)+(x-y)=a(x-y)+(x-y)=a(x-y)+1(x-y)=(x-y)(a+1) ax-y+x-ay=(ax-ay)+(-y+x)=(ax-ay)+(x-y)=a(x-y)+(x-y)=a(x-y)+1(x-y)=(x-y)(a+1)](https://tex.z-dn.net/?f=ax-y%2Bx-ay%3D%28ax-ay%29%2B%28-y%2Bx%29%3D%28ax-ay%29%2B%28x-y%29%3Da%28x-y%29%2B%28x-y%29%3Da%28x-y%29%2B1%28x-y%29%3D%28x-y%29%28a%2B1%29)
======================================================================
![ax-2bx+ay-2by=(ax+ay)+(-2bx-2by)=(ax+ay)-(2bx+2by)=a(x+y)-2b(x+y)=(x+y)(a-2b) ax-2bx+ay-2by=(ax+ay)+(-2bx-2by)=(ax+ay)-(2bx+2by)=a(x+y)-2b(x+y)=(x+y)(a-2b)](https://tex.z-dn.net/?f=ax-2bx%2Bay-2by%3D%28ax%2Bay%29%2B%28-2bx-2by%29%3D%28ax%2Bay%29-%282bx%2B2by%29%3Da%28x%2By%29-2b%28x%2By%29%3D%28x%2By%29%28a-2b%29)
======================================================================
Задание № 3
![mx+my+6x+6y=(mx+my)+(6x+6y)=m(x+y)+6(x+y)=(x+y)(m+6) mx+my+6x+6y=(mx+my)+(6x+6y)=m(x+y)+6(x+y)=(x+y)(m+6)](https://tex.z-dn.net/?f=mx%2Bmy%2B6x%2B6y%3D%28mx%2Bmy%29%2B%286x%2B6y%29%3Dm%28x%2By%29%2B6%28x%2By%29%3D%28x%2By%29%28m%2B6%29)
======================================================================
![9x+ay+9y+ax=(9x+9y)+(ay+ax)=(9x+9y)+(ax+ay)=9(x+y)+a(x+y)=(x+y)(9+a) 9x+ay+9y+ax=(9x+9y)+(ay+ax)=(9x+9y)+(ax+ay)=9(x+y)+a(x+y)=(x+y)(9+a)](https://tex.z-dn.net/?f=9x%2Bay%2B9y%2Bax%3D%289x%2B9y%29%2B%28ay%2Bax%29%3D%289x%2B9y%29%2B%28ax%2Bay%29%3D9%28x%2By%29%2Ba%28x%2By%29%3D%28x%2By%29%289%2Ba%29)
======================================================================
![7a-7b+an-bn=(7a-7b)+(an-bn)=7(a-b)+n(a-b)=(a-b)(7+n) 7a-7b+an-bn=(7a-7b)+(an-bn)=7(a-b)+n(a-b)=(a-b)(7+n)](https://tex.z-dn.net/?f=7a-7b%2Ban-bn%3D%287a-7b%29%2B%28an-bn%29%3D7%28a-b%29%2Bn%28a-b%29%3D%28a-b%29%287%2Bn%29)
======================================================================
![ax+ay-x-y=(ax+ay)+(-x-y)=(ax+ay)-(x+y)=a(x+y)-(x+y)=a(x+y)-1(x+y)=(x+y)(a-1) ax+ay-x-y=(ax+ay)+(-x-y)=(ax+ay)-(x+y)=a(x+y)-(x+y)=a(x+y)-1(x+y)=(x+y)(a-1)](https://tex.z-dn.net/?f=ax%2Bay-x-y%3D%28ax%2Bay%29%2B%28-x-y%29%3D%28ax%2Bay%29-%28x%2By%29%3Da%28x%2By%29-%28x%2By%29%3Da%28x%2By%29-1%28x%2By%29%3D%28x%2By%29%28a-1%29)
======================================================================
![1-bx-x+b=(1+b)+(-bx-x)=(1+b)+(-x-bx)=(1+b)-(x+bx)=(1+b)-x(1+b)=1(1+b)-x(1+b)=(1+b)(1-x) 1-bx-x+b=(1+b)+(-bx-x)=(1+b)+(-x-bx)=(1+b)-(x+bx)=(1+b)-x(1+b)=1(1+b)-x(1+b)=(1+b)(1-x)](https://tex.z-dn.net/?f=1-bx-x%2Bb%3D%281%2Bb%29%2B%28-bx-x%29%3D%281%2Bb%29%2B%28-x-bx%29%3D%281%2Bb%29-%28x%2Bbx%29%3D%281%2Bb%29-x%281%2Bb%29%3D1%281%2Bb%29-x%281%2Bb%29%3D%281%2Bb%29%281-x%29)
======================================================================
![xy+2y-2x-4=(xy+2y)+(-2x-4)=(xy+2y)-(2x+4)=y(x+2)-2(x+2)=(x+2)(y-2) xy+2y-2x-4=(xy+2y)+(-2x-4)=(xy+2y)-(2x+4)=y(x+2)-2(x+2)=(x+2)(y-2)](https://tex.z-dn.net/?f=xy%2B2y-2x-4%3D%28xy%2B2y%29%2B%28-2x-4%29%3D%28xy%2B2y%29-%282x%2B4%29%3Dy%28x%2B2%29-2%28x%2B2%29%3D%28x%2B2%29%28y-2%29)